The Effect of Implementing the Learning Model to Develop Metacognitive Ability (PMKM) on Learning Outcomes and Learning Independence of Ninth Grade Junior High School Mathematics Students - Abdul Rahman; Sukarna Sukarna; Muh. Hidayatullah Dwi Putra (PT Mattawang Mediatama Solution, 2023)
This study aims to determine the effect of Learning to Develop Metacognitive Ability (PMKM) model on learning outcomes and students' independence in learning mathematics. This research is pre-experimental study conducted in class IX use cluster random sampling with 24 students as the research sample. Data collection was carried out using a learning achievement test and learning independence questionnaire. The data analysis technique used are descriptive and inferential statistical analysis techniques. The results of descriptive statistical analysis are: (1) The average score of student learning outcomes before the application of PMKM model is 24.57 which is in very low category, (2) The average score of student learning outcomes after the application of PMKM model is 86.71 which means is in high category, (3) the independence of student learning before the application of the PMKM model is in fairly independent category or with average score of 41.75, (4) the independence of student learning after the application of the PMKM model is in independent category or with average score 62,20. Meanwhile, the results of inferential statistical analysis show that the application of PMKM model has a positive effect on learning outcomes and learning independence of class IX junior high school students.